Profile of microbial community of organic and conventional rice field using metagenomic analysis - Arum Asri Trisnastuti; Edi Purwanto; Ari Susilowati (Biogenesis: Jurnal Ilmiah Biologi, 2021)
Organic farming can increase the diversity of soil bacterial. This research aimed to compare the profile of microbial community of organic and conventional rice fields in early (0 Day After Planting/DAP), mid (15 DAP), and late (45 DAP) fertilizer application period. The total DNA genome from the soil sample was extracted then analyzed metagenomically using Next Generation Sequencing (NGS). There was nine genus of bacteria found in high relative abundance, 95.28%, while 4.72% included in Domain of Archaea (genus Methanosaeta). Phylum of Firmicutes (genus Clostridium has 24.50% relative abundance, Bacillus 11.90%, Lactobacillus 9.69%); Proteobacteria (genus Defluviicoccus 12.10%, Buchnera 18.46%, Rosenbergiella 2.46%); and Actinobacteria (genus Nocardioides 12.21%, and Streptomyces 3.96%). Meanwhile, the average plant height of organic rice fields was shorter than conventional rice fields got directly measured coincided with soil sampled. Based on alpha and beta diversity analysis, the highest community diversity and abundance were found in organic rice field soil samples taken at 45 DAP, i.e., at the end of the fertilizer application period. However, in both organic and conventional rice field soils, there was almost no significant difference in the bacterial community, so it impacts that organic and conventional systems do not make a real difference in the total N, P available, CEC, and pH values. It makes a significant difference in organic C and organic matters.